Bulbar impairment score and survival of stable amyotrophic lateral sclerosis patients after noninvasive ventilation initiation. Issue 2 (16th April 2018) - Sancho, Jesús; Martínez, Daniel; Bures, Enric; Díaz, José Luis; Ponz, Alejandro; Servera, Emilio
There is general agreement that noninvasive ventilation (NIV) prolongs survival in amyotrophic lateral sclerosis (ALS) and that the main cause of NIV failure is the severity of bulbar dysfunction. However, there is no evidence that bulbar impairment is a contraindication for NIV. The aim of this study was to determine the effect of bulbar impairment on survival in ALS patients with NIV. ALS patients for whom NIV was indicated were included. Those patients who refused NIV were taken as the control group. 120 patients who underwent NIV and 20 who refused NIV were included. The NIV group presented longer survival (median 18.50 months, 95% CI 12.62–24.38 months) than the no-NIV group (3.00 months, 95% CI 0.82–5.18 months) (p<0.001) and also in those patients with severe bulbar dysfunction (13.00 months (95% CI 9.49–16.50 months) v ersus 3.00 months (95% CI 0.85–5.15 months), p<0.001). Prognostic factors for ALS using NIV, adjusted for NIV failure, were severity of bulbar dysfunction (hazard ratio (HR) 0.5, 95% CI 0.92–0.97; p=0.001) and time spent with oxygen saturation measured by pulse oximetry <90% (%sleep S pO2 <90) using NIV (HR 1.12, 95% CI 1.01–1.24; p=0.02). Severe bulbar impairment in ALS does not always prevent NIV from being used, but the severity of bulbar dysfunction at NIV initiation and %sleep S pO2 <90 while using NIV appear to be the main prognostic factors of NIV failure in ALS. NIV prolongs survival in some ALS patients with severe bulbar impairment at NIV indication http://ow.ly/vFr530iCwnj